Investigating Demographic Variations in the Use of Online Public Services: A UTAUT-Based Multigroup Analysis - Thi My Dieu Nguyen; Van Bau Nguyen (Ital Publication, 2026)
This study aims to investigate demographic disparities in the adoption of online public services (OPS) in Vietnam, a nation experiencing rapid digital transformation while grappling with unequal access. Employing the Unified Theory of Acceptance and Use of Technology (UTAUT) as the analytical framework, data from 1,186 citizens were analyzed using PLS-SEM and multigroup analysis to determine whether the fundamental UTAUT relationships differ across these demographic segments. The findings indicate that women are more affected by family and community encouragement; ethnic minority users place greater reliance on performance expectancy “valuing time savings, reduced travel, and service accessibility” and rural users depend more on effort expectancy and facilitating conditions due to infrastructure constraints. These differences affirm that social and contextual factors significantly influence citizens’ behavioral intentions toward OPS use. The study’s novelty lies in incorporating demographic segmentation into the UTAUT framework within a developing-country context, thereby extending its theoretical applicability and providing actionable insights for an inclusive digital government. The results offer policymakers evidence-based guidance for designing targeted interventions to enhance accessibility and equity in Vietnam’s digital transformation process.